2018
DOI: 10.1002/jsfa.9394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorine dioxide (ClO2) on patulin produced by Penicillum expansum and involved mechanism

Abstract: BACKGROUND Patulin, produced by Penicillium expansum in apple fruit, has side effects affecting human and animal health. The effect of chlorine dioxide (ClO2) on patulin production, and the mechanisms involved in this, were investigated. RESULTS Patulin production by P. expansum was reduced by ClO2 treatment, both in apples and in a potato dextrose broth (PDB) medium, which was attributed to the antifungal effect of ClO2, but not the direct reaction between ClO2 and patulin. Fumigation with ClO2 also significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Zhang and Fu (2018) noted that patulin production in both apple juice and potato dextrose broth (PDB) medium was observably decreased as the concentration (100-400 mg L −1 ) of ClO 2 increased. Nevertheless, the degradation rate of pure patulin in an apple juice reduced slightly after ClO 2 treatment at different concentrations (Zhang et al 2018a).…”
Section: Toxins Degradation Mechanismsmentioning
confidence: 93%
“…Zhang and Fu (2018) noted that patulin production in both apple juice and potato dextrose broth (PDB) medium was observably decreased as the concentration (100-400 mg L −1 ) of ClO 2 increased. Nevertheless, the degradation rate of pure patulin in an apple juice reduced slightly after ClO 2 treatment at different concentrations (Zhang et al 2018a).…”
Section: Toxins Degradation Mechanismsmentioning
confidence: 93%
“…Although, as expected, the SOA composition depends on the concentration of oxidizing agents, humidity, and temperature. 139–141 Ehn and co-workers had shown that HOM formation decreased about 50 percent when experiments were performed at 0 °C compared to 20 °C. 142 While the molecular formulae and structures of some of the primary products of the photooxidation reactions have been identified, many mechanistic details, reaction intermediates, and reaction end products have not been definitively characterized, but there has been considerable interest in understanding the SOA in recent years.…”
Section: α-Pinene In Atmospheric Chemistrymentioning
confidence: 99%
“…Some organic acids are beneficial for patulin decontamination, such as ascorbic acid, which can remarkably increase the degradation of patulin when combined with heating treatment (Kokkinidou, Floros, & LaBorde, 2014). Zhang, Fu, and Chen (2019) reported that chlorine dioxide (ClO 2 ) treatment could reduce patulin contamination, but the effect was mainly dependent on the inhibition of P. expansum infection, not direct degradation.…”
Section: Control Technologiesmentioning
confidence: 99%